Gyrinicola chabaudi Araujo & Artigas, 1982 (Nematoda: Pharyngodonidae) in tadpoles of Scinax nasicus (Cope, 1862) (Anura: Hylidae) from Corrientes, Argentina - Gonzalez, Cynthya Elizabeth (2005)
Gyrinicola chabaudi (Pharyngodonidae) represents a new record for the country and is reported for the first time from hylid tadpoles of Scinax nasicus. Fifteen anurans were collected in a pond located 30 km from Corrientes City, province of Corrientes, Argentina (27°28’S - 58°50’W) in May 2000. The nematode infection was detected in 66 % of tadpoles